El ministro Lora Tamayo y la universidad - Torres Parra, María José (Historia de las Universidades, 2021)
The focus of this work is the figure of Manuel Lora Tamayo, Minister of Education between 1962 and 1968, years in which Spain's incorporation into the international concert forced the Franco regime to reinterpret itself. Lora Tamayo, faced with the consequences of an educational policy that was miserly in terms of investment and impregnated with Francoist ideology, wanted to materialise the symmetry between economic progress and education, thus following the postulates of the technocracy that he defended. The reform programme affected all levels of education, but it was at the university level - of particular importance to the author - where the changes were especially relevant. Lora wanted a university model with modern structures, with new categories of teaching staff and where the teaching-research binomial would mark university work. Resistance to some of Lora Tamayo's proposed changes was aggravated by the difficult relations between the university - and its contradictory internal life - and the confrontation of interests of the powers that be, which underpinned Franco's regime and whose underground struggle clouded the Spanish educational and cultural panorama.